#TITLE_ALTERNATIVE# - Banda Selamat NIM. 25198503, Muhammad
Abstrak: In Indonesia, the exploration of tuna only takes 14% of its maximum sustainable yields. The use of spatial information technology is one of the realistic way to increase the exploration of this commodity. This research have two main objectives, first objective is to design the data base with manage the daily tuna catching data. Second objective is to produce the tuna fishing ground map based on satelite estimate. Sea Surface Temperature (SST) is the important factor that regulate fish living process and its distribution. Each tuna has specific SST for its activities. SST could be estimated from NOAA-AVHRR satellite based on the basic assumption that every object emits electromagnetic energy according to its temperature, wave length dan emisivity. The establishment of data base had been design with four entities, those are day, position, the vessel and catching. The implementation of this model can provide both textual and spatial information for tuna catching activites. The estimated tuna fishing ground areas are derived by querying the data base and assigning spesific criteria for tuna SST classes and its hook rate.